1990
DOI: 10.1002/ptr.2650040304
|View full text |Cite
|
Sign up to set email alerts
|

Eugenol a valuable compound for in vitro experimental research and worthwhile for further in vivo investigation

Abstract: Eugenol and isoeugenol are responsible for several pharmacological activities exhibited by nutmeg preparations. We studied their antimicrobial and antiaggregation activity in &fro and their influence on platelet tunction ex vivo. At the same time biogenetically or metabolically related derivatives were tested. Eugenol and isoeugenol (1 mg/mL) showed pronounced antibacterial properties: growth inhibition of 6 out of 10 Gram + and Gram -microorganisms was comparable with neomycin (500 pg/mL). Growth inhibition w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
53
0
5

Year Published

2002
2002
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 85 publications
(58 citation statements)
references
References 29 publications
0
53
0
5
Order By: Relevance
“…Eugenol belongs to a class of phenylpropenes. Free hydroxyl groups confer the antimicrobial activity of this class (Laekeman et al, 1990). The antimicrobial activity of eugenol can be attributed to the presence of a double bond in α, β positions of the side chain and to a methyl group located in the γ position (Jung and Fahey, 1983).…”
Section: Motility Testmentioning
confidence: 99%
“…Eugenol belongs to a class of phenylpropenes. Free hydroxyl groups confer the antimicrobial activity of this class (Laekeman et al, 1990). The antimicrobial activity of eugenol can be attributed to the presence of a double bond in α, β positions of the side chain and to a methyl group located in the γ position (Jung and Fahey, 1983).…”
Section: Motility Testmentioning
confidence: 99%
“…Wie et al (1997) reported that eugenol reversed neuronal excitotoxic or oxidative injury and had protective effect against N-methyl-D-aspartate-induced neurotoxicity. [22][23][24][25][26][27][28][29]. Eugenol induced cell lysis of Gram-negative and Gram-positive bacteria by damaging the cell wall and membrane caused leakage of protein and lipid contents (Figure 4) [29].…”
Section: Antioxidant Activity Of Eugenolmentioning
confidence: 99%
“…Among the 30 tested Chinese herbal medicines which are used traditionally for treating gastritis-like disorders, the ethanol extracts of E. caryophyllus were strongly inhibitory to all the six H. pylori strains (Li et al, 2005). Eugenol, the main component of E. caryophillis oil, is a phenolic compound and is proven to be active against many pathogenic bacteria (Laekeman et al, 2006;Xu et al, 2013), fungi (Laekeman et al, 2006), and viruses (Tragoolpua & Jatisatienr, 2007). In one study, eugenol completely inhibited all the strains (both sensitive and resistant) at a concentration of 2 mg/mL.…”
Section: Eugenia Caryophyllusmentioning
confidence: 99%